SISTEM PAKAR DIAGNOSA KESEHATAN MENTAL MENGGUNAKAN METODE NAÏVE BAYES BERBASIS ANDROID - Mustaqim, Ladzina; Annurrullah Fajrin, Alfannisa (LPPM Universitas Putera Batam, 2025)
Artificial Intelligence (AI) is a branch of computer science that creates systems capable of performing tasks that require human intelligence. This development of an Android-based expert system is aimed at diagnosing mental health issues, specifically depression, in individuals aged 15 to 25. The system integrates Naïve Bayes and forward chaining methods to analyze symptom data and health history, classifying the severity of depression into mild, moderate, and severe categories. The development process includes data analysis, information gathering through interviews and literature studies, as well as creating a user-friendly application prototype. Testing results indicate that the system provides accurate and rapid diagnoses, helping users understand their mental health conditions, enhancing accessibility to diagnosis, reducing stigma, and supporting the prevention and management of depression more effectively.